The Effect Of Position Rotation On Employee Work Productivity At The Fisheries Service Office Bulukumba Regency - Rahmat Hidayat; Sitti Nurbaya; Sitti Marhumi (International Journal of Economic Research and Financial Accounting, 2024)
This research utilizes a quantitative approach to explore the relationship between job rotation and work productivity within the Fisheries Department of Bulukumba Regency. Regression analysis indicates a significant relationship between the job rotation variable (X) and work productivity (Y), with a regression coefficient of 0.902 and a very high level of significance (< 0.001). The results show that each one-unit increase in job rotation is associated with an increase of 0.902 units in work productivity. The regression model also demonstrates a high level of fit, with a coefficient of determination of 0.911, indicating that approximately 91.1% of the variation in work productivity can be explained by the job rotation variable. These findings are consistent with the theory that job rotation can enhance employee productivity and can be utilized to assess employee potential and increase motivation through activity variation. These results support the use of job rotation as a significant predictor of improved work productivity in the context of the Fisheries Department of Bulukumba Regency. Effective implementation and management of job rotation strategies can be key to enhancing employee work productivity.